1,2,4-Triphenylpyrroles: Synthesis, Structure and Luminescence Properties - Ferreira, Joana R. M.; Nunes da Silva, Raquel; Rocha, João; Silva, Artur M. S.; Guieu, Samuel (Synlett, 2020)
Pyrroles are widely found in natural products and play an important role in biological processes. Certain pyrrole derivatives are fluorescent and may be used as molecular probes or biomarkers in the diagnosis of diseases, such as Alzheimer’s or Parkinson’s. Herein is reported the synthesis of five new pyrrole derivatives bearing phenyl rings on positions 1, 2, and 4, with electron-donating groups at the periphery. The introduction of more or stronger electron-donating groups red-shifts and increases the efficiency of the fluorescence emission.
Keywords: triphenylpyrroles; Nef reaction; Paal–Knorr reaction; fluorescence; crystal structure